2020
DOI: 10.5037/jomr.2020.11405
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Infraorbital Canal Protrusion into Maxillary Sinus Using Cone-Beam Computed Tomography

Abstract: Objectives The aim of this retrospective study was to evaluate the relation of the infraorbital canal course with the maxillary sinus using cone-beam computed tomography. Material and Methods A total of 1000 infraorbital canals (IOC) were examined from 500 cone-beam computed tomography scans. IOCs were classified into three types based on the degree of protrusion into the sinus. The presence of Haller cells and mucosal thickening in the sinus were evaluated. The length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Recent studies have revealed that this finding was not as rare as previously thought, with a prevalence in the literature ranging from 8.8% to 15.7%. 4 5 6 7 10 13 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have revealed that this finding was not as rare as previously thought, with a prevalence in the literature ranging from 8.8% to 15.7%. 4 5 6 7 10 13 …”
Section: Discussionmentioning
confidence: 99%
“…In the reporting of this retrospective cross-sectional study, the RECORD statement - a checklist extended from the STROBE reporting guidelines for observational studies - was followed. Assuming an 8.8% prevalence of protruded IOCs (a figure based on the findings of Kalabalik et al 7 ), a total of 123 sinuses were needed for a margin of error of 5% and a 95% confidence interval. Sample size was calculated using Epi Info statistical software (version 7; Centers for Disease Control and Prevention, Atlanta, GA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations